Model Strategi Diplomasi Budaya di Masa Covid-19 : Studi Kasus Festival Cap Go Meh di Kota Singkawang - Nurfitri Nugrahaningsih; Widha Anistya Suwarso (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2021)
This study aims to identify the cultural diplomacy strategy carried out by Singkawang City Government during Covid-19 pandemic. Singkawang has a Cap Go Meh festival which is held every year which attracts the attention of domestic and foreign tourists. The Covid-19 pandemic has spread over the world since the end of 2019 and gave impacts on many sectors, including the number of tourist visits to Cap Go Meh in Singkawang City, West Kalimantan in 2021. This research was conducted through a qualitative approach with an exploratory method and refers to cultural diplomacy and digital diplomacy concept. The results of this study indicate that there are models of cultural diplomacy during pandemic: (1) The cooperation and commitment from government and non-government actors to support and promote cultural diplomacy, (2) The implementation of e-diplomacy, and (3) There are strict regulations related to the Covid-19 pandemic; however, still provide space for cultural diplomacy. Keywords: Cap Go Meh, Covid-19, cultural diplomacy, digital diplomacy